Runaway bride [videorecording (DVD)] - Marshall, Garry; Roberts, Julia, 1967-; Gere, Richard, 1949-; Wilson, Rita (Paramount, 1999)
An unlikely love story developes when a cynical, big-city columnist comes to a small town to cover the story of Maggie Carpenter, a bride who's left men at the altar several times.